Aplikasi FTIR sebagai Deteksi Cepat Bahan Non-Halal dalam Campuran Produk Olahan - Mabrurotul Mustafidah; Arif Nur Ikhsan (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2022)
The trend of Halal is not about label processed products, but also to become a necessity in products to gain public trust. Indonesia as the country with the most Muslims in Asia, has its own market for halal products. Consumer confidence increases for goods that have included halal in their products. The unknown material in this case is the material that makes the product non-halal, such as the presence of a mixture of pork. Many irresponsible producers use a mixture of non-halal ingredients to increase profits. To detect halal, various methods have been developed, one of which is FTIR. FTIR is a fast and easy to use instrument capable of analyzing mixtures in a product. Various studies for product authentication were analyzed using FTIR and showed results that FTIR was able to detect the presence of a mixture of unwanted ingredients in the product and could be used as a method to detect counterfeiters in processed products.